Growth and the Geography of Knowledge - Marta Aloi; Joanna Poyago-Theotoky; Frederic Tournemaine (Center for Economic Studies and ifo Institute (CESifo), 2018)
We analyse how spatial disparities in innovation activities, coupled with migration costs, affect economic geography, growth and regional inequality. We provide conditions for existence and uniqueness of a spatial equilibrium, and for the endogenous emergence of industry clusters. Spatial variations in knowledge spillovers lead to spatial concentration of more innovative firms. Migration costs, however, limit the concentration of economic activities in the most productive region. Narrowing the gap in knowledge spillovers across regions raises growth, and reduces regional inequality by making firms more sensitive to wage differentials. The associated change in the spatial concentration of industries has positive welfare effects.
Keywords: O41; O31; L13; J61; R32; 330; growth; economic geography; geographic labour mobility; innovation; knowledge spillovers; regional economics